2018
DOI: 10.7554/elife.40037
|View full text |Cite
|
Sign up to set email alerts
|

The RNA interactome of human telomerase RNA reveals a coding-independent role for a histone mRNA in telomere homeostasis

Abstract: Telomerase RNA (TR) provides the template for DNA repeat synthesis at telomeres and is essential for genome stability in continuously dividing cells. We mapped the RNA interactome of human TR (hTR) and identified a set of non-coding and coding hTR-interacting RNAs, including the histone 1C mRNA (HIST1H1C). Disruption of the hTR-HIST1H1C RNA association resulted in markedly increased telomere elongation without affecting telomerase enzymatic activity. Conversely, over-expression of HIST1H1C led to telomere attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 88 publications
(141 reference statements)
2
13
0
Order By: Relevance
“…We showed that disruption of TERC regions complementary to terc-sRNA impaired association between AGO2 and TERC. In line with our data, it was recently shown that TERC can interact with different RNA molecules by direct RNA-RNA base pairing and predicted interaction sites fall mostly within regions spanning terc-sRNA target sites in CR4/CR5 and in the TBE domains, suggesting that these regions are prone to form RNA duplexes [91]. Therefore, we hypothesize that terc-sRNA might recognize TERC by base complementarity and recruit AGO2 to TERC.…”
Section: Terc-interacting Proteins: the Usual And Unusual Suspectssupporting
confidence: 91%
“…We showed that disruption of TERC regions complementary to terc-sRNA impaired association between AGO2 and TERC. In line with our data, it was recently shown that TERC can interact with different RNA molecules by direct RNA-RNA base pairing and predicted interaction sites fall mostly within regions spanning terc-sRNA target sites in CR4/CR5 and in the TBE domains, suggesting that these regions are prone to form RNA duplexes [91]. Therefore, we hypothesize that terc-sRNA might recognize TERC by base complementarity and recruit AGO2 to TERC.…”
Section: Terc-interacting Proteins: the Usual And Unusual Suspectssupporting
confidence: 91%
“…Aside from the protein-related product, a 15-nt long region in the ORF region (nt334–nt348) is attributed to HIST1H1C -mRNA-mediated biological activity, through complementation with the terminal stem-loop sequence of the P6b region of hTR, in a base-pairing pattern. These results extend the functional potency of mRNA ORF regions in a non-traditional and noncoding direction (Ivanyi-Nagy et al, 2018).…”
Section: Noncoding Rna Regulatory Functions Embedded In Mrnassupporting
confidence: 73%
“…Human telomerase is a ribonucleoprotein complex with an endogenous RNA template, which catalyzes the extension of hexamer DNA repeats . In a majority of human cancers, telomerase is upregulated or reactivated, which leads to indefinite proliferation of cancer cells .…”
Section: Methodsmentioning
confidence: 99%